2016
DOI: 10.1080/10962247.2016.1231144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of titania nanotubes and titanium dioxide as supports of low-temperature selective catalytic reduction catalysts under sulfur dioxide poisoning

Abstract: A series of iron-manganese oxide catalysts supported on TiO and titanium nanotubes (TNTs) were studied for low temperature selective catalytic reduction (SCR) of NO with NH in the presence of SO The results showed that the specific surface area and the amount of Brønsted acid sites were highly correlated. The results also demonstrated that higher Mn/Mn ratios and larger specific surface areas might be the main reasons for the excellent performance of MnFe-TNTs catalyst after SO poisoning. The SO poisoning effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The TNTs were also used to tune the redox property and adsorption ability of Mn–Ce composite oxides, and thus high LT activity and N 2 selectivity could be achieved . TNTs supported Fe–Mn oxide catalysts exhibited better SO 2 tolerance than TiO 2 supported ones, however, the LT SO 2 -resistant mechanism for this catalyst was not illustrated …”
Section: Metal Oxide Catalystsmentioning
confidence: 99%
“…The TNTs were also used to tune the redox property and adsorption ability of Mn–Ce composite oxides, and thus high LT activity and N 2 selectivity could be achieved . TNTs supported Fe–Mn oxide catalysts exhibited better SO 2 tolerance than TiO 2 supported ones, however, the LT SO 2 -resistant mechanism for this catalyst was not illustrated …”
Section: Metal Oxide Catalystsmentioning
confidence: 99%
“…Orthogonal experimental results suggested that the optimum preparation conditions for the biochar materials were biochar carbon material, nitric acid, an acid/mass ratio of 1.50 and a pyrolysis temperature of 800°C. It has been well documented over the past several years that MnOx based catalysts provide high low temperature SCR performance compared with other metal oxides (Liu et al, 2016;Lee et al, 2017;Liu et al, 2017). In this reported work, the optimum carbon biochar material was used as a carrier to support the active catalyst component (MnO x ).…”
Section: Low Temperature Scr Performance Of the Supported Biochar Catalystsmentioning
confidence: 99%
“…However, when reaction temperature increased, the SCR reaction mechanism would transform from Langmuir−Hinshelwood mechanism to Eley-Rideal mechanism. In our previous work [32], it was found that the gradual decrease (stage II) of NO consumption in the SCR reaction was probably due to the fact that SO 2 competed with NO to react with NH 3 and form ammonium salts. However, the MnFe/TiO 2 catalyst still had good activity at stage III.…”
Section: Scr Reactions With Somentioning
confidence: 95%
“…To understand the products and byproducts of oxidation reactions, the NH 3 and NO oxidation reactions over the MnFe/TiO 2 catalyst were studied within the temperature range of 100-300 • C, which was the most active temperature region for MnFe/TiO 2 catalyst in SCR reaction [32]. In addition, the N-balance of NH 3…”
Section: Oxidation Reactions Of Nh 3 and No Without Somentioning
confidence: 99%